HISTOPATHOLOGICAL KIDNEY OVERVIEW OF EXPERIMENTAL DIABETES MELLITUS WISTAR RATS GIVEN ETHANOL EXTRACT OF MORINGA LEAF - Kamaliani, Baiq Renny; Setiasih, Ni Luh Eka; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2019)
This study aims to prove that the Moringa leaf extract can improve renal histological structure of diabetic Wistar rats. Wistar rats were divided into six groups, so that each group has four replications. K1 as the positive control was not given the extract, K2 was administered the extract dose 100 mg/kg, K3 was administered the extract dose 200 mg/kg, K4 was administered the extract dose 300 mg/kg, K5 was administered the extract dose 400 mg/kg, K6 was administered the extract dose 500 mg/kg. The administrations of extract were held for five weeks. Rats then sacrificed and the kidneys were taken for the histopathology preparations with Hematoxylin-Eosin staining (HE). The observations indicate fatty degeneration and necrosis of the kidneys. Kruskal Wallis test results of all treatments showed p = 0.001 in both fatty degeneration and necrosis (p <0.05).